2018
DOI: 10.1590/1678-4499.2017119
|View full text |Cite
|
Sign up to set email alerts
|

Two independent grain-length mutants mapped to a single region on the long arm of chromosome 2 in rice

Abstract: ABSTRACT:Grain shape in rice is a key determinant of grain appearance, yield and market value, and thus has been widely studied. Rice mutant lines with long-grain phenotypes were previously isolated from an M 2 population derived from mutagenized mature pollen grains that were treated with gamma-ray irradiation for a cultivar Ma85. To understand the genetic basis underlying the long-grain trait, two mutant lines, JF171 and JF178, were crossed with the short-grain parents JF222 and Samba, generating three F 2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Zhu Yiqiao (Zhu.,2022) studied the impact of pit excavation on existing railroad tunnels in soft soil areas and found that soft soil pit excavation next to the existing railroad will cause significant impacts, unreasonable construction will aggravate the degree of impacts, the use of "zonal excavation, the installation of additional protective structures" can effectively reduce the impact on the existing railroad. To obtain reasonable design parameters when crossing the existing tunnels nearby, the ground displacement calculation method considering the coexistence of hydraulic expansion and infiltration and diffusion modes of the slurry was introduced, and a coupled calculation model of the deformation response of the grouting construction and the neighboring existing tunnels was established (Jiang et al,2024). For the construction deformation characteristics of loess tunnels, the deformation law and mechanical characteristics of large section loess tunnel cutter shield construction under the influence of different burial depths are proposed (Jiang et al,2023).…”
Section: Introductionmentioning
confidence: 99%
“…Zhu Yiqiao (Zhu.,2022) studied the impact of pit excavation on existing railroad tunnels in soft soil areas and found that soft soil pit excavation next to the existing railroad will cause significant impacts, unreasonable construction will aggravate the degree of impacts, the use of "zonal excavation, the installation of additional protective structures" can effectively reduce the impact on the existing railroad. To obtain reasonable design parameters when crossing the existing tunnels nearby, the ground displacement calculation method considering the coexistence of hydraulic expansion and infiltration and diffusion modes of the slurry was introduced, and a coupled calculation model of the deformation response of the grouting construction and the neighboring existing tunnels was established (Jiang et al,2024). For the construction deformation characteristics of loess tunnels, the deformation law and mechanical characteristics of large section loess tunnel cutter shield construction under the influence of different burial depths are proposed (Jiang et al,2023).…”
Section: Introductionmentioning
confidence: 99%